18F-FDG PET CT as a prognostic factor in hepatocellular carcinoma - Cho, Eunae; Jun, Chung-Hwan; Kim, Ban-Seok; Son, Dong-Jun; Choi, Won-Suk; Choi, Sung-Kyu (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: To elucidate the role of 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG-PET/CT) imaging as an independent prognostic factor in hepatocellular carcinoma (HCC). Materials and Methods: A total of 104 patients with newly diagnosed HCC who underwent 18F-FDG-PET/CT imaging from 2009 to 2014 were reviewed retrospectively. The ratio of the maximal tumor standardized uptake value (SUV) to the mean mediastinum SUV (TSUVmax/MSUVmean) was evaluated as the predictive factor. Results: A high TSUVmax/MSUVmean ratio (≥3.1) was significantly associated with tumor burden indices, including α-fetoprotein (p<0.001), amino transaminase (AST) (p=0.007), tumor size (p=0.043), Tumor, Node, and Metastasis (TNM) stage (p<0.001), and Barcelona Clinic Liver Cancer (BCLC) staging (p<0.001). The mortality rate was higher (48.1% vs. 23.1%, p<0.001) in patients with a high TSUVmax/MSUVmean ratio (≥3.1). Among the 47 patients who underwent transarterial chemoembolization (TACE), patients with a high TSUVmax/MSUVmean ratio (≥3.1) were more likely to have recurrence following TACE (18/19 vs. 18/28, p=0.016). Conclusion: A high TSUVmax/MSUVmean ratio on 18F-FDG-PET/CT imaging can serve as an independent prognostic factor in HCC and may predict tumor recurrence after TACE.